Extrusion cooking : cereal grains processing - Ganjyal, Girish M. (Woodhead Publishing, 2020)
Extrusion Cooking provides a detailed description of extrusion processing with an in-depth exploration of cereal grains processing. In particular, the book addresses the basic principles of extrusion processing, various extruder parts and their design principles, food ingredients and their characteristics as they relate to extrusion. It also discusses physicochemical changes in the different ingredient components as they are processed in an extruder, modeling and control of extrusion process, scale-up aspects, extrusion plant design, food safety in extrusion, new advancements in extrusion, and a look into the future of extrusion. This valuable text serves as a one-volume reference on extrusion processing for food industry professionals and students. --